2015
DOI: 10.1073/pnas.1507063112
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and selective molecular catalyst for the CO 2 -to-CO electrochemical conversion in water

Abstract: Substitution of the four paraphenyl hydrogens of iron tetraphenylporphyrin by trimethylammonio groups provides a watersoluble molecule able to catalyze the electrochemical conversion of carbon dioxide into carbon monoxide. The reaction, performed in pH-neutral water, forms quasi-exclusively carbon monoxide with very little production of hydrogen, despite partial equilibration of CO 2 with carbonic acid-a low pK a acid. This selective molecular catalyst is endowed with a good stability and a high turnover frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
292
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 307 publications
(304 citation statements)
references
References 38 publications
11
292
1
Order By: Relevance
“…Furthermore, suitable functional groups can be introduced to the porphyrin rings to adjust the redox potential and pKa. [73] It is important to note that Shen et al also found the production of small amounts of CH 4 and CH 3 OH originating from CO further reduction [69] and they claimed that the CO further reduction conformed to coupled proton-electron transfer. [72] …”
Section: Decoupling Of Proton and Electron Transfermentioning
confidence: 98%
“…Furthermore, suitable functional groups can be introduced to the porphyrin rings to adjust the redox potential and pKa. [73] It is important to note that Shen et al also found the production of small amounts of CH 4 and CH 3 OH originating from CO further reduction [69] and they claimed that the CO further reduction conformed to coupled proton-electron transfer. [72] …”
Section: Decoupling Of Proton and Electron Transfermentioning
confidence: 98%
“…[4,5] These catalysts are mainly active in aprotic solvent with reaction products being mostly CO and more rarely HCOOH. [9,10] In that case,C O production was achieved with over 90 %selectivity at neutral pH and am oderate 450 mV overpotential. Ni cyclam was first reported as as elective and efficient catalyst of the CO 2 -to-CO conversion in water at am ercury surface electrode,with favorable specific interactions of the catalytic adsorbed species with the surface, [6,7] while the use of acarbon electrode leads to much less efficiencyi nt erms of rate (maximal turnover frequency of 90 s À1 )a nd turnover (4 cycles).…”
mentioning
confidence: 93%
“…Hence, CO 2 reduction/activation by 3 d metal‐based catalysts has received intense interest. Among noteworthy examples of homogeneous catalysts are Fe‐tetraphenylporphyrin and derivatives by Savéant and co‐workers, selective reduction of CO 2 to formate using [Fe 4 N(CO) 12 ] – by Berben and co‐workers, and reduction of CO 2 to methanol by borane with Ni and Fe pincer complexes by Guan and co‐workers . Li and co‐workers reported photo‐reduction of CO 2 to CO catalyzed by molecular Co complexes immobilized on solid support .…”
Section: Introductionmentioning
confidence: 99%